Implementasi Komunikasi Antarbudaya pada Perkawinan Antarbudaya bagi Pasangan Suami Istri Mualaf di Kuta Bali - Safara, Deli Melia; Najikh, Ahmad Hayyan (Icon: Islamic Communication and Contemporary Media Studies, 2024)
Islam forbid marriage if the husband and wife are not in the same religion. Therefore, some couples decide to convert when they are getting married. This causes cultural differences between couples due to different religious backgrounds. The conflicts faced by the couple will be more difficult due to cultural differences. If it cannot be resolved, then a divorce may occur in the household. The focus of this research is to find out the intercultural communication strategies of intercultural marriage couples for husband and wife converts in Kuta Bali. This study used a qualitative research method with a descriptive qualitative approach. The result of this study is that the communication strategy used by the informants in maintaining harmony in household life is to fully know the character of each partner so that they know each other the effective communication patterns that must be used to partners. In addition, there needs to be tolerance for each couple for their respective families because of cultural differences. Adjustments also need to be made for each couple because there are differences in life before and after marriage. In this study, it was concluded that the informants were already in the stable exchange stage, namely between individuals who understood each other, felt comfortable so that they dared to be fully open to each other so that the level of ambiguity was getting smaller, both in terms of thoughts, behavior and feelings towards their respective partners.